O processo de (re)construção de objetos de discurso em esquetes do coletivo criativo "Porta dos fundos" - Lima, Dean Guilherme Gonçalves (2017)
This work intends to describe and analyze, in the socio-historical perspectives of Bakhtin´s Circle (1988, 2003, 2008) and Marcuschi (20002, 2008), the organization and functionality of the discursive genre sketch, especially those elaborated by the humoristic creative “Porta dos Fundos” (Backdoor). Furthermore, it proposes to investigate, considering the integration of verbal and visual elements in this genre, how the processes of construction and reconstruction of objects of the discourse are carried out. In addition, it explores the role of the referential processes of humor production. In this regard, theoretical and methodological principles are drawn upon the works of Mondada and Dubois (2003), Cavalcante (2011, 2012, 2015), Cavalcante e Lima (2013), Lima (2009), Ciulla e Silva (2008), Costa (2007), Leite (2007), Tavares (2003), Raskin (1985), Raskin e Attardo (1991), Lins (2015), Lins e Gonçalves (2013), Tafarello (2014), Travaglia (2015) and Possenti (1998, 2015). The corpus consists of six sketches in which the main topic is a taboo, such as sex, prostitution and homoaffectivity. This choice is justified by the relevance of works that pursue the characterization of the genre “sketches” and the necessity of investigating the referential processes in multi-semiotic texts. The non-exclusivity of the verbal element in the (re)elaboration of objects of the discourse can be observed in this study. In order to produce humor, the linguistic and imagistic signs work together, without overlapping one another, (re)elaborating the referents.